On the asymptotic behavior of the diameter of the image of a ball at infinity - Klishchuk, B.; Salimov, R.; Stefanchuk, M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We study the asymptotic behavior of the diameter of the image of a ball under ring $Q$-homeomorphisms with respect to the $p$-modulus for $p>n$ in the space $\mathbb{R}^{n}$, $n≥ 2$. We also establish the lower bound for the distortion of the diameter of ball image and solve extremal problems of minimization of the functionals of distortion of the diameter of ball image on some classes of ring $Q$-homeomorphisms with respect to the $p$-modulus.